2001
DOI: 10.1016/s0092-8674(01)00205-7
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the RNA Component of RNase MRP Cause a Pleiotropic Human Disease, Cartilage-Hair Hypoplasia

Abstract: The recessively inherited developmental disorder, cartilage-hair hypoplasia (CHH) is highly pleiotropic with manifestations including short stature, defective cellular immunity, and predisposition to several cancers. The endoribonuclease RNase MRP consists of an RNA molecule bound to several proteins. It has at least two functions, namely, cleavage of RNA in mitochondrial DNA synthesis and nucleolar cleaving of pre-rRNA. We describe numerous mutations in the untranslated RMRP gene that cosegregate with the CHH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
326
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(357 citation statements)
references
References 40 publications
16
326
0
4
Order By: Relevance
“…They speculated that deregulation of these genes and the pathway that they were part of, could be the causative abnormality in 5q-syndrome patients. This idea was supported by previous findings that genetic defects of ribosomal genes were implicated in congenital anemias including dyskeratosis congenita, 12 cartilage-hair hypoplasia, 13 DiamondBlackfan anemia 14 and Shwachman-Diamond syndrome. 15,16 The importance of RPS14 haplo-insufficency as a causative event in 5q-syndrome was then shown by Ebert et al using RNAi to selectively inhibit each of the 40 genes within the deleted region.…”
supporting
confidence: 61%
“…They speculated that deregulation of these genes and the pathway that they were part of, could be the causative abnormality in 5q-syndrome patients. This idea was supported by previous findings that genetic defects of ribosomal genes were implicated in congenital anemias including dyskeratosis congenita, 12 cartilage-hair hypoplasia, 13 DiamondBlackfan anemia 14 and Shwachman-Diamond syndrome. 15,16 The importance of RPS14 haplo-insufficency as a causative event in 5q-syndrome was then shown by Ebert et al using RNAi to selectively inhibit each of the 40 genes within the deleted region.…”
supporting
confidence: 61%
“…60 In 2001, Ridanpää et al identified mutations in the untranslated RMRP gene as causative for this pleiotropic disease, with an ancient founder mutation in Finland. 61 RMRP encodes the RNA component of the mitochondrial RNA processing complex (RNase MRP), which is primarily located in the nucleolus and is classified as a snoRNA. snoRNAs form small nucleolar ribonucleoprotein complexes (snoRNPs) within the nucleolus and are involved in various steps in the synthesis of ribosomal RNA.…”
Section: Cartilage Hair Hypoplasiamentioning
confidence: 99%
“…By inference, it is assumed that the RNA subunit of MRP is also responsible for catalysis (13). MRP is also an essential endonuclease (52,53) that processes mostly rRNA, but also some mRNAs and other substrates (Table 2).…”
Section: Function and Substratesmentioning
confidence: 99%